A Facile Hydroxyindole Carboxylic Acid Based Focused Library Approach for Potent and Selective Inhibitors of Mycobacterium Protein Tyrosine Phosphatase B. Issue 6 (8th April 2013) - Zeng, Li‐Fan; Xu, Jie; He, Yantao; He, Rongjun; Wu, Li; Gunawan, Andrea M.; Zhang, Zhong‐Yin
Abstract : Focused on Mtb : A facile hydroxyindole carboxylic acid based focused amide library was designed to target both the PTP active site and a unique nearby pocket for enhanced affinity and selectivity. HTS of the library led to the identification of a highly potent and selective inhibitor, 11 a, of mPTPB, an essential virulence factor for Mycobacterium tuberculosis. Compound11 a shows high cellular activity and is capable of reversing the altered immune responses induced by mPTPB in macrophages.